Mucinous cystic neoplasm of the pancreas with type-1 autoimmune pancreatitis-like lesion - Kevin Gowing; David F. Schaeffer; Hui-Min Yang (Elsevier, 2019)
Mucinous cystic neoplasm (MCN) is characterized by mucinous epithelial lining and subepithelial ovarian-like stroma and is a precursor to invasive carcinoma. Type 1 autoimmune pancreatitis (AIP), on the other hand, is a form of IgG4-related disease (IgG4-RD) and can present as a pancreatic mass. There is no known causal relationship between these two entities in the current literature. Here, we report a case of a middle-aged female patient who was found to have an enlarging pancreatic mass and subsequently underwent a distal pancreatectomy. Gross examination of the pancreatectomy specimen showed a 4.3 cm mass with a central 3.4 cm cystic component, confirmed to be an MCN on microscopy. The immediately adjacent peritumoral tissue showed storiform fibrosis, obliterative phlebitis, and focal IgG4-positive plasma cell-rich infiltrates (≥75/HPF) with an IgG4+/IgG+ ratio of 80%. The background pancreas was histologically normal and these characteristic AIP findings were limited to the pericystic tissue. Clinical workup with CT scan and MRI did not show any evidence of systemic IgG4-RD, nor was the serum IgG4 level ever elevated. To our knowledge, this is only the second reported case of a pancreatic MCN associated with peritumoral AIP-like changes in a patient without systemic IgG4-RD. Awareness of these potential AIP-like changes surrounding pancreatic neoplasms may be helpful in preventing misdiagnosis in needle biopsy and aspiration specimens. Keywords: Type 1 autoimmune pancreatitis, IgG4-related disease, IgG4-RD, IgG4-related pancreatitis, Mucinous cystic neoplasm, MCN, Sclerosing pancreatitis